2023
DOI: 10.1007/s11356-023-26321-w
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the effectiveness of dust control measures adopted to reduce workplace exposure

Abstract: The recent increase in silicosis cases in several countries casts doubt on dust control practices and their effectiveness in preventing respirable crystalline silica (RCS) exposure. Apart from silicosis, RCS may lead to other illnesses, health-related quality of life losses for workers and their families, and economic losses for companies. Thus, this systematic literature review examined the effectiveness of interventions employed to prevent exposure to RCS and increase the use of dust control measures. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 138 publications
(148 reference statements)
0
3
0
Order By: Relevance
“…Dust exposure control is the only way to prevent workers from developing silica-related diseases; as highlighted above, dust control measures range in their effectiveness according to the hierarchy of controls. However, the effectiveness of these methods is also dependent on how they are used and/or maintained by workers, which in turn is associated with the knowledge, attitudes and behaviour of workers in workplaces [ 55 , 56 ]. A range of studies in different countries such as Vietnam [ 57 ], India [ 58 , 59 ], Spain [ 60 ], and China [ 61 ] consistently demonstrated that educated workers who are given adequate information and training were likely to be aware of the harmful outcomes of occupational exposure to silica dust [ 56 ], and therefore more willing to comply with health standards and regulations [ 62 , 63 ].…”
Section: The Hostmentioning
confidence: 99%
“…Dust exposure control is the only way to prevent workers from developing silica-related diseases; as highlighted above, dust control measures range in their effectiveness according to the hierarchy of controls. However, the effectiveness of these methods is also dependent on how they are used and/or maintained by workers, which in turn is associated with the knowledge, attitudes and behaviour of workers in workplaces [ 55 , 56 ]. A range of studies in different countries such as Vietnam [ 57 ], India [ 58 , 59 ], Spain [ 60 ], and China [ 61 ] consistently demonstrated that educated workers who are given adequate information and training were likely to be aware of the harmful outcomes of occupational exposure to silica dust [ 56 ], and therefore more willing to comply with health standards and regulations [ 62 , 63 ].…”
Section: The Hostmentioning
confidence: 99%
“…Nonetheless, owing to the open-air mining environment, such operations precipitate substantial dust pollution (Luo et al, 2016). To address this issue, open-pit mines conventionally resort to dust suppression techniques such as water spraying, foam dust removal, and the application of chemical dust suppressants (Liu et al, 2021;Anlimah et al, 2023). While these dust control technologies deliver moderate amelioration, they are accompanied by the following drawbacks: water spraying not only squanders signi cant quantities of freshwater resources but also has its dust suppression e cacy contingent on meteorological conditions; foam dust removal introduces new chemical pollutants, engendering secondary contamination ; and chemical dust suppressants, with their inherent toxicity, irritancy, and corrosivity, coupled with poor degradability, fall short of meeting the standards for green mining practices (Wang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The ingress of construction dust into water bodies can deteriorate water quality. Therefore, control of air dusting is one of the main approaches to ensure external environmental safety of construction [19]. Various methods are used for this purpose: moistening of surfaces, creation of various barriers preventing spread of dust, etc.…”
mentioning
confidence: 99%